History of Los Alamos Participation in Active Experiments in Space - Pongratz, Morris B. (Frontiers in Physics, 2018)
Los Alamos has a long history of participation in active experiments in space beginning with the Teak nuclear test in 1958. Above-ground nuclear testing stopped in 1962 because of the Partial Test Ban Treaty, and a program of non-nuclear chemical release experiments began in 1968. Los Alamos has participated in nearly 100 non-nuclear experiments in space, the last being the NASA-sponsored strontium and europium doped barium thermite releases in the Arecibo beam in July of 1992. The rationale for these experiments ranged from studying basic plasma processes such as gradient- driven structuring and velocity-space instabilities to illuminating the convection of plasmas in the ionosphere and polar cap to ionospheric depletion experiments to the B.E.A.R. 1-MeV neutral particle beam (NPB) test in 1989. This report reviews the objectives, techniques and diagnostics of Los Alamos participation in active experiments in space.